(untitled) (Experimental biology, 2023)
The article describes the work on the route calculation of pests that occur in the cotton field sown in different periods in the practice of peasant farms of Turkestan region. In a directional study, it was found that the cotton moth settled in cotton fields on an average of 1 m2 – 0.5-2 pieces. In the conditions of the Turkestan region, 18-20 pieces per 100 plants were found in the cotton crop, when exceeding the threshold of economic harmfulness against pests Dimilin 48% s.k., (0.1 L/ha), Tagrel e.k., (1.5 l/ha); Lyatrin e. k., (0.5 l/ha); Petra 5% e.k., (0.5 l/ha); Karate, 050 e.k., (0.5 l/ha) ha) spraying was carried out. The prevalence of cotton root rot was 1.5% -11%, the development was 1.0 - 12%, and the prevalence and development of cotton gommosis was 1-3%.